Proceeding of Proceedings of the 9th International Symposium on Radiative Transfer, RAD-19 2019
DOI: 10.1615/rad-19.380
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Use of Symbolic Monte Carlo for Conduction-Radiation Coupling in Complex Geometries

Abstract: We address the interest of using Symbolic Monte Carlo to obtain a reduced model for conduction-radiation coupling in complex geometries. Symbolic Monte Carlo was successfully used for radiative transfer in a decoupled manner, but no attempt has yet been reported to extend its use to radiation coupled with other modes. Here we show that from a unique Monte Carlo simulation of radiation coupled with conduction in a semi-transparent solid surrounded by a convective flow, it is possible to build a formulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In order to achieve this, one needs to express the kinetic rate constant, k E , as an expected value. The question is open, but recent studies showed that the temperature could be expressed as an expected value in k E .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve this, one needs to express the kinetic rate constant, k E , as an expected value. The question is open, but recent studies showed that the temperature could be expressed as an expected value in k E .…”
Section: Resultsmentioning
confidence: 99%
“…For future investigations, the coupling of chemical kinetics with a thermal model (such as a heat equation) will be considered. This is a concept that has already been demonstrated in radiation physics by coupling the radiative transfer to the absorption coefficient model, while other research coupling heat transfer phenomena is ongoing. …”
Section: Discussionmentioning
confidence: 99%
“…The complete methodology and the particular configuration of the flash method are detailed. Compared to previous studies [25][26][27], the present problem requires a transient solution. Thus, a validation case is provided for a 3D geometry which could be useful as a benchmark case for further algorithmic improvements.…”
Section: Introductionmentioning
confidence: 96%
“…This approach has been validated for conductive and radiative transfers by comparison with a deterministic method. Ibarrart et al [26] extended this to consider coupled conductive, advective and radiative heat transfers while Penazzi et al [27] studied the case of a semi-transparent medium. Assuming the linearity of heat transfers is a not limiting factor because only a small increase of the equilibrium temperature of the medium is required in most of the characterization methods, including the flash method.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the SMC method was previously developed only for radiative heat transfer. Recent developments have now extended the use of this method to combined heat transfer [Penazzi, 2019]. Previously, [Villefranque, 2019] showed the insensitivity of computation time to mesh refinements for the resolution of radiative transfer with the MC method in the field of atmospheric radiation.…”
Section: Introductionmentioning
confidence: 99%